An Intrauterine Complete Perineal Tear in a Female Neonate, A Rare Birth Injury Related to Breech Presentation: A Case Report - Gautam, Sarika; Shivangi; Singhal, Savita; Kadian, Yogender; Dalal, Monika; Gupta, Anjali; Tomar, Neetu (Journal of College of Medical Sciences-Nepal, 2023)
Birth injuries are wounds that a newborn receives when being delivered, whether vaginally or via lower segment caesarean section. It is a case of a 39-week pregnant female with foetal distress and breech presentation in labour who was received in the emergency labour room as a referral case after multiple per vaginal examinations done by a staff nurse at a peripheral hospital, with a complaint of leaking and bleeding per vaginum since then. Her emergency LSCS was done in view of foetal distress with breech presentation. A female baby was extracted and found to have a complete perineal tear in an otherwise healthy neonate. Her paediatric surgeon's opinion was sought, and a complete perineal tear was done in layers with Vicryl 3-0 sutures. On follow-up, the female neonate was continent and thriving well. Unintended vaginal examinations during breech presentation could result in an intrauterine complete perineal tear if the examiner is untrained. If these injuries are identified immediately and prompt management is done, it may lead to lesser morbidity and a better quality of life.